(untitled) (Hematology Meeting Reports, 2009)
Mantle cell lymphoma (MCL) represents approximately 8% of cases of non-Hodgkin’s lymphoma (NHL) and is an incurable, aggressive B-cell malignancy. The disease usually presents in an advanced stage and commonly involves extranodal sites such as the gut, bone marrow, and peripheral blood. Most patients are older adults and there is a male predominance. The characteristic tumor cell immunophenotype is a population of CD20+, CD10-, CD5+, CD23- B-cells with monoclonal light chain expression on the cell surface.